2006
DOI: 10.1016/j.jacc.2006.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Intracoronary Cellular Cardiomyoplasty for Nonischemic Cardiomyopathy: Clinical and Histopathological Results: The First-in-Man ABCD (Autologous Bone Marrow Cells in Dilated Cardiomyopathy) Trial

Abstract: To the Editor: Stem cell therapy has shown potential benefit in heart failure caused by ischemic heart disease (1). There is no data on the role of stem cell therapy in nonischemic dilated cardiomyopathy. We undertook a pilot study of intracoronary stem cell implantation in patients with dilated cardiomyopathy.From a cohort of 44 patients, 24 were randomly allocated to the stem cell therapy arm and 20 to the control arm. All patients were having dilated cardiomyopathy with an ejection fraction (EF) of Յ35%, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 4 publications
3
83
3
1
Order By: Relevance
“…Furthermore, Seth et al (19) have reported identical mortality in a cell therapy trial for patients with non-ischemic dilated cardiomyopathy. Considering the time interval between the procedure and the occurrence of deaths by pulmonary edema and cardiogenic shock, the severity of the heart failure of the patients at enrollment and the natural history of the disease, we consider these deaths most likely not to be related to the cell injection procedure.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, Seth et al (19) have reported identical mortality in a cell therapy trial for patients with non-ischemic dilated cardiomyopathy. Considering the time interval between the procedure and the occurrence of deaths by pulmonary edema and cardiogenic shock, the severity of the heart failure of the patients at enrollment and the natural history of the disease, we consider these deaths most likely not to be related to the cell injection procedure.…”
Section: Discussionmentioning
confidence: 93%
“…No adverse events have been reported in a trial where mononuclear cells were delivered to the coronary arteries in 24 patients after coronary sinus occlusion (19). Another trial used the intramyocardial route to deliver cells during thoracotomy, but only 5 IDC patients were included in the trial that reported 7 episodes of ventricular fibrillation during the procedure and 2 deaths by the same mechanism during the perioperative period (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And indeed, MSC transplantation was associated with significantly increased capillary density and decreased collagen volume fraction in the myocardium, resulting in an improved cardiac function. The first-in-man study was performed by Seith et al (121). Forty-four patients with an ejection fraction 35%, normal coronary arteries, and New York Heart Association (NYHA) functional class II or more were randomly assigned to a stem cell therapy arm (24 patients) or a control arm (20 patients).…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…Both demonstrated improved EF. 87,88 Cell Type Comparisons ASC had favorable results in APOLLO and PRECISE. Both trials demonstrated the efficacy of ASC in AMI and left ventricular dysfunction in settings of marked myocardial ischemia.…”
Section: Dilated Cardiomyopathymentioning
confidence: 98%